The Influence of Artificial Intelligence (AI) Use on Students’ Learning Motivation and Independence in the Era of the Merdeka Curriculum - Anshori, Muhammad; Aquino, Joseph (Lembaga Publikasi Ilmiah Nusantara, 2026)
The rapid integration of Artificial Intelligence (AI) into educational practices has introduced new opportunities for strengthening student-centered learning, particularly within the framework of Indonesia’s Merdeka Curriculum. This study investigates the influence of AI-based learning tools on students’ learning motivation and independence in secondary schools. Employing a mixed-methods design, data were collected through surveys involving 210 students and semi-structured interviews with teachers who have implemented AI applications such as adaptive learning platforms, automated feedback systems, and AI-supported tutoring tools. Quantitative analysis using multiple regression reveals that the use of AI has a significant and positive effect on both learning motivation and learning independence. Students reported greater engagement, personalized learning experiences, and improved self-regulated learning behaviors when interacting with AI-enhanced instructional tools. Qualitative findings further indicate that AI helps students develop autonomy by enabling them to set their own pace and access individualized feedback. However, challenges such as uneven digital literacy, limited infrastructure, and teachers’ readiness to integrate AI remain obstacles to optimal implementation. Overall, the study highlights that AI has substantial potential to support the principles of the Merdeka Curriculum - especially freedom to learn and differentiated instruction - provided that adequate training and technological support are ensured.